Early-life pain alters excitability of corticotropin-releasing factor-expressing neurons in the central amygdala and stress-induced hypersensitivity during adolescence - Tomasch, Megan; Naess, Emma; McComas, Skyler; Burman, Michael A. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionNeonatal intensive care units (NICUs) provide life-saving care for preterm and sick neonates, but many medical procedures are painful and stress-inducing. Even a routine NICU procedure, such as the “heel lancing” blood-draw procedure, is an acutely painful, repetitive manipulation that has lasting negative impacts on pain perception and anxiety responses. The intersection of nociception and negative affect occurs in a brain region called the central nucleus of the amygdala (CeA), and neurons expressing corticotropin-releasing factor (CRF) have been implicated in studies of both anxiety and pain.MethodsUsing a two-hit model of trauma-induced pain vulnerability—where repetitive needle prickings occur during the first week of life (“our NICU model”), followed by a second stressor (e.g., fear conditioning) during adolescence—our lab has observed a mechanical hypersensitivity in rats that endured our NICU model that manifests only after fear conditioning. We have also observed changes to expression and activation of CeA-CRF neurons after the NICU-like experience with an acute increase followed by a lasting reduction in the number of CRF cells in the right CeA of adolescent male rats. However, the relationship between these changes and the observed behavioral outcomes remains unclear, as does the function of the remaining CRF cell population. We hypothesize that the remaining population of CRF-expressing CeA neurons are functionally altered by early life pain and stress and primed to respond more readily, such that vulnerability to stress-induced hypersensitivity is increased.ResultsThrough chemogenetic inhibition of the amygdala, or specifically CeA-CRF neurons, we demonstrate that development of stress-induced mechanical hypersensitivity after our NICU model is completely reversed through silencing the amygdala. Inhibiting only CeA-CRF neurons during fear conditioning led to a partial reversal of the hypersensitivity, suggesting that other populations of cells also play critical roles. Nevertheless, we demonstrate that the NICU-like experience results in a lasting hyperexcitability of CeA-CRF neurons during adolescence, confirming that this population is affected by the early life manipulations.DiscussionIn all, this study suggests that CeA-CRF neurons may have pro-nociceptive properties that are exacerbated by early life pain and result in maladaptive responding to subsequent traumatic events.